Effectiveness of a headache awareness campaign on behavioral change - Muraoka, Shinsuke; Asai, Takumi; Suzuki, Naoki; Nishizawa, Toshihisa; Nishida, Kazuki; Chrétien, Basile; Saito, Ryuta (Frontiers in Neurology, 2025)
Headache is a significant public health issue due to its high prevalence, associated disability, and socioeconomic burden. In Japan, awareness of migraine prevention and the risks of medication overuse remains limited. This study examined whether increasing knowledge about headaches through an online educational campaign could lead to behavioral changes, such as more frequent visits to headache clinics and reduced misuse of headache medications. An online educational program on headaches was conducted for 1,829 hospital staff members, who first completed a questionnaire before watching an educational video. Six months later, they completed a second questionnaire to assess behavioral changes. The initial survey revealed that although headaches interfered with work and daily life for approximately 50% of participants, only 20% regularly sought medical care. The most common reason for not visiting a medical facility was reliance on over-the-counter medications. In the follow-up survey, 20% of participants had independently gathered information about headaches, 6% had visited a medical institution for a new headache, and 40% had reduced their use of painkillers after becoming aware of medication overuse headache (MOH). A decision tree model, using the reduction in painkiller use as the outcome, indicated that correct knowledge about migraine, including preventive treatments, and active information-seeking behavior were key factors in promoting behavioral change. These findings suggest that providing online headache education to hospital staff may contribute to improved headache management by increasing awareness of migraine prevention and MOH while reducing excessive painkiller use.